Developing organizational resilience with the mediating role of leader – Member exchange - Putra, Yanuar Surya; Istiyani, Ambar (Goodwood Publishing, 2022)
Purpose: The purpose of this research is to investigate the effect of social capital and organizational flexibility toward organizational resilience, with the mediating role of leader – member exchange (LMX) in higher education institutions in Salatiga, Central Java, Indonesia. Research methodology: This research will be conducted in Salatiga by taking a total number of lecturers at three higher education organizations in Salatiga, the samples were taken 245 lecturers and educational personnel. This study used purposive_sampling as a sampling technique, and the analysis instrument is path_analysis with Partial Least Square (PLS) using SmartPLS. Results: The direct effect indicates that social capital and organizational flexibility positively influence organizational resilience, and LMX mediates the relation between_social_capital_and_organizational flexibility towards organizational resilience_in higher education institutions in Salatiga. Limitations: The limitation of this study, is that this study only took lecturers and educational personnel as research samples, while to determine organizational resilience, it required the involvement of all organizational components, besides that the exogenous variables selected were limited to individual and organizational variables. Contribution: The results of this study contribute to the field of management, especially human resource management, specifically this research provides input to increase organizational resilience through the development and the activity to manage social_capital_and_organizational flexibility, involving the role of leader-member in the organization.